Precortical Phase of Alzheimer's Disease (AD)‐Related Tau Cytoskeletal Pathology. (24th August 2015) - Stratmann, Katharina; Heinsen, Helmut; Korf, Horst‐Werner; Del Turco, Domenico; Ghebremedhin, Estifanos; Seidel, Kay; Bouzrou, Mohamed; Grinberg, Lea T.; Bohl, Jürgen; Wharton, Stephen B.; den Dunnen, Wilfred; Rüb, Udo
Abstract: Alzheimer's disease (AD) represents the most frequent progressive neuropsychiatric disorder worldwide leading to dementia. We systematically investigated the presence and extent of the AD‐related cytoskeletal pathology in serial thick tissue sections through all subcortical brain nuclei that send efferent projections to the transentorhinal and entorhinal regions in three individuals with Braak and Braak AD stage 0 cortical cytoskeletal pathology and fourteen individuals with Braak and Braak AD stage I cortical cytoskeletal pathology by means of immunostainings with the anti‐tau antibody AT8. These investigations revealed consistent AT8 immunoreactive tau cytoskeletal pathology in a subset of these subcortical nuclei in the Braak and Braak AD stage 0 individuals and in all of these subcortical nuclei in the Braak and Braak AD stage I individuals. The widespread affection of the subcortical nuclei in Braak and Braak AD stage I shows that the extent of the early subcortical tau cytoskeletal pathology has been considerably underestimated previously. In addition, our novel findings support the concept that subcortical nuclei become already affected during an early 'pre‐cortical' evolutional phase before the first AD‐related cytoskeletal changes occur in the mediobasal temporal lobe (i.e. allocortical transentorhinal and entorhinal regions). The very early involved subcortical brain regions may represent the origin of the AD‐related tau cytoskeletal pathology, from where the neuronal cytoskeletal pathology takes an ascending course toward the secondarily affected allocortex and spreads transneuronally along anatomical pathways in predictable sequences.